2017
DOI: 10.1074/jbc.m116.773986
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear factor erythroid 2-related factor 2 enhances carcinogenesis by suppressing apoptosis and promoting autophagy in nickel-transformed cells

Abstract: Nickel-containing compounds are widely used in industry. Nickel is a known human carcinogen that primarily affects the lungs. Proposed mechanisms of nickel-induced carcinogenesis include disruption of cellular iron homeostasis, generation of reactive oxygen species (ROS), and induction of hypoxia signaling. However, the precise molecular mechanisms of nickel-induced malignant transformation and tumor development remain unclear. This study shows that the transcription factor Nrf2 is highly expressed in lung tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 66 publications
0
12
1
Order By: Relevance
“…A recent study has suggested that NRF2 upregulates the transcription of Stat3 as one of the target genes (45). However, this scenario does not seem applicable to our result, because STAT3 phosphorylation is promoted without any increase in the amount of total STAT3 protein in Keap1-deficient HSPCs.…”
Section: Discussioncontrasting
confidence: 53%
“…A recent study has suggested that NRF2 upregulates the transcription of Stat3 as one of the target genes (45). However, this scenario does not seem applicable to our result, because STAT3 phosphorylation is promoted without any increase in the amount of total STAT3 protein in Keap1-deficient HSPCs.…”
Section: Discussioncontrasting
confidence: 53%
“…Thus, the disruption of the Nrf2-Keap1 pathway can suppress autophagy while autophagy deficiency leads to the overexpression of the Nrf2-Keap1 pathway. The regulation and co-ordination of Keap1–Nrf2 and the autophagy pathway are essential for cell growth, differentiation, redox signaling and survival, has been addressed in several studies [ 205 , 206 ]. A recent investigation showed that during prolonged exposure of oxidative stress, using tert-butyl hydroperoxide (TBHP), Nrf2 negatively regulates autophagy through the down-regulation of AMPK [ 207 ].…”
Section: The Relationship Between Reactive Oxygen Species and Autophamentioning
confidence: 99%
“…Son et al 32 used nickel-transformed BEAS-2B cells and showed increased LC3II levels and overexpression of Stat3, a protein with a promoter region that has an ARE binding site. When Stat3 levels were suppressed, a reduction in LC3II level was found, while Nrf2 suppression resulted in depletion of Stat3, indicating that Nrf2 exerts an influence on the sensitivity of autophagy.…”
Section: Scientific Reports |mentioning
confidence: 99%